«Zugrunde gehen». The Metaphor and the Archaeology in Freudian Psychoanalysis - Caranci Sáez, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Taking as a pretext the American Imago’s monograph of 2021 dedicated to the so-called «archaeological metaphor», first used by Freud in 1896 to illustrate his pioneering analytical praxis, this article attempts, firstly, to denote the limits of some of the studies on the matter. Secondly, by reviewing the evolution in the use of archaeological analogies in Freud’s work, we hope to demonstrate their true value. On one hand, by considering the theory of fantasies, which questions the veracity of the contents from the past in the patient’s psyche. On the other, looking into the dialectic work of psychoanalysis itself, which does not pretend to excavate the site —the analysand’s discourse, the symptomatic body— but to remain on its surface, locating the zero point of its formal articulation.